Analisis Kelemahan Rezim European Union Emission Trading Scheme dalam Menghadapi Carousel Fraud pada Tahun 2010 â€“ 2015 - Wibowo, Muhammad Faris Hersanda; Wahyudi, Fendy Eko (Journal of International Relations, 2018)
European Union Emission Trading Scheme as the world largest carbon trading regime, has launched in 2005. From 2005 until now EU ETS has been pass three phase, which every period has a significant change on EU ETS regime. Carousel fraud is one of fraud which harms European union member states, in EU ETS carousel fraud is make EU country loss their GDP until 5 billion euro in 2011. EU ETS regime is struggling to counter this fraud, in order to secure their member states from carousel fraud in the future EU ETS through European Commision recommend anti-fraud mechanism which every country should implement. But not all states comply with the recommendation from European Commision. This research is struggling to find out why not all EU ETS member states comply with European Commission recommendation. For the record, EU ETS is â€œclassicâ€ fraud which also happens in many Europe commodity market. This research purpose is to find out why there is no consensus among EU member states. This research uses qualitative research method with international regime theory and compliance theory to analyze regime and states behavior. According to the result of this research, national interest is the main reason why states not meet the consensus, non-states actor also playing significant rules in EU ETS and them also responsible for carousel fraud which happens in EU ETS.